Thyrotoxicosis after iodine fortification. A 21‐year Danish population‐based study. (27th June 2018) - Petersen, Mads; Knudsen, Nils; Carlé, Allan; Andersen, Stig; Jørgensen, Torben; Perrild, Hans; Ovesen, Lars; Rasmussen, Lone Banke; Thuesen, Betina Heinsbæk; Pedersen, Inge Bülow
Summary: Objective: Monitoring the influence of cautious iodine fortification (IF) on the incidence rate of overt thyrotoxicosis in Denmark with formerly frequent multinodular toxic goitre. Design: A 21‐year (1997‐2017) prospective population‐based study identified all new cases of overt biochemical thyrotoxicosis in two open cohorts: a Western cohort with moderate iodine deficiency (ID) and an Eastern cohort with mild ID (total n = 533 969 by 1 January 1997). A diagnostic algorithm was applied to all thyroid function tests performed within the study areas. Mandatory IF of salt was initiated in mid‐2000 (13 ppm). This study is a part of DanThyr. Results: The standardized incidence rate (SIR) of thyrotoxicosis at baseline (1997‐1998) was 128.5/100.000/year in the cohort with moderate ID and 80.1 in the cohort with mild ID. SIR increased markedly in both cohorts during the initial years of IF (moderate/mild ID: +39/+52% in 2000‐2001/2004‐2005) and subsequently decreased to baseline level (mild ID) or below (moderate ID) by 2008. The decline was due to a marked decrease in the incidence rate among elderly subjects and a moderate decrease among the middle aged. The follow‐up period for the mildly iodine deficient cohort was restricted to 2008. A continuous decline in SIR was observed for the remainder of the study period in the area with moderate ID (33% below baseline in 2016‐2017). Conclusion: The rise in thyrotoxicosis incidence with cautious mandatory IF returned to baseline level after 7‐8 years and levelled out at 33% below baseline in the population with previously moderate ID after 16‐17 years.